Characterization and Diversity Analysis of the Extracellular Proteases of Thermophilic Anoxybacillus caldiproteolyticus 1A02591 From Deep-Sea Hydrothermal Vent Sediment - Cheng, Jun-Hui; Wang, Yan; Zhang, Xiao-Yu; Sun, Mei-Ling; Zhang, Xia; Song, Xiao-Yan; Zhang, Yu-Zhong; Zhang, Yi; Chen, Xiu-Lan (Frontiers in Microbiology, 2021)
Protease-producing bacteria play key roles in the degradation of marine organic nitrogen. Although some deep-sea bacteria are found to produce proteases, there has been no report on protease-secreting Anoxybacillus from marine hydrothermal vent regions. Here, we analyzed the diversity and functions of the proteases, especially the extracellular proteases, of Anoxybacillus caldiproteolyticus 1A02591, a protease-secreting strain isolated from a deep-sea hydrothermal vent sediment of the East Pacific Ocean. Strain 1A02591 is a thermophilic bacterium with a strong protease-secreting ability, which displayed the maximum growth rate (0.139 h-1) and extracellular protease production (307.99 U/mL) at 55°C. Strain 1A02591 contains 75 putative proteases, including 65 intracellular proteases and 10 extracellular proteases according to signal peptide prediction. When strain 1A02591 was cultured with casein, 12 proteases were identified in the secretome, in which metalloproteases (6/12) and serine proteases (4/12) accounted for the majority, and a thermolysin-like protease of the M4 family was the most abundant, suggesting that strain 1A02591 mainly secreted a thermophilic metalloprotease. Correspondingly, the secreted proteases of strain 1A02591 showed the highest activity at the temperature as high as 70°C, and was inhibited 70% by metalloprotease inhibitor o-phenanthroline and 50% by serine protease inhibitor phenylmethylsulfonyl fluoride. The secreted proteases could degrade different proteins, suggesting the role of strain 1A02591 in organic nitrogen degradation in deep-sea hydrothermal ecosystem. These results provide the first insight into the proteases of an Anoxybacillus strain from deep-sea hydrothermal ecosystem, which is helpful in understanding the function of Anoxybacillus in the marine biogeochemical cycle.